THE USE OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TECHNIQUE ON STUDENTS’ READING COMPREHENSION - Eva Mariana; Entis Sutisna; Asih Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
Reading comprehension is the process of getting the main purpose of the text during reading. Students not only can read the whole passage but also comprehend and understand what the important point of the text is. However, the difficulty of comprehending text during reading is a problem for students. Cooperative Integrated Reading and Composition (CIRC) technique is the solution to solve the problem. The aim of this research is to investigate the use of Cooperative Integrated Reading and Composition (CIRC) technique on students’ reading comprehension. In conducting this research, the writer applied pre-experimental method and one group pretest and posttest design. This research is conducted to the first semester students of English Language Education Study Program, Faculty of Teacher Training and Educational Sciences, Pakuan University. There were 20 students as the sample of this research by using random sampling. The result shows that based on t-table, the degree of freedom of 19 at significant level of 0.05 is 2.09. However, the value of t-test is 3.89. From the comparison between the value of t-test and the t-table, it can be concluded that the value of t-test is higher than t-table (3.89 more than 2.09). Thus, the alternative hypotheses of this research (Ha) is accepted. Therefore, CIRC technique affects students’ reading comprehension..